1991
DOI: 10.1212/wnl.41.8.1197
|View full text |Cite
|
Sign up to set email alerts
|

Seizures caused by nontraumatic parenchymal brain hemorrhages

Abstract: Seizures occurred in 15% of patients with parenchymal brain hemorrhage (early in 12% and delayed in 3%). Seizures were most frequent with lobar hemorrhages and uncommon with deep subcortical hemorrhages. Lobar hemorrhages in the frontal, parietal, or temporal region were more commonly associated with seizures, whereas occipital hemorrhages were not. Seizures were most common if the hemorrhage was due to an aneurysm, angioma, or neoplasm and less common if hypertensive or spontaneous. If the patient had recurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
4
3

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 0 publications
1
26
4
3
Order By: Relevance
“…Thus, there was continued uncertainty in assessing the incidence of chronic epilepsy/unprovoked seizures after spontaneous ICH in nonselected patients Several authors have reported variables related to seizures after spontaneous ICH. 4,3,9,14,15,19,22 Cerebral hemorrhages giving rise to seizures were predominantly cortical in location, 3,10,16,19,22 although two-thirds of seizures arose from deep cerebral hemorrhages in our study (in 12 patients), a figure lower than previous studies. 3,19,22 Our study demonstrated that presence of cortical hemorrhage was predictive of seizures.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…Thus, there was continued uncertainty in assessing the incidence of chronic epilepsy/unprovoked seizures after spontaneous ICH in nonselected patients Several authors have reported variables related to seizures after spontaneous ICH. 4,3,9,14,15,19,22 Cerebral hemorrhages giving rise to seizures were predominantly cortical in location, 3,10,16,19,22 although two-thirds of seizures arose from deep cerebral hemorrhages in our study (in 12 patients), a figure lower than previous studies. 3,19,22 Our study demonstrated that presence of cortical hemorrhage was predictive of seizures.…”
Section: Discussioncontrasting
confidence: 81%
“…4,3,9,14,15,19,22 Cerebral hemorrhages giving rise to seizures were predominantly cortical in location, 3,10,16,19,22 although two-thirds of seizures arose from deep cerebral hemorrhages in our study (in 12 patients), a figure lower than previous studies. 3,19,22 Our study demonstrated that presence of cortical hemorrhage was predictive of seizures. The authors of several studies 4,22 have noted that neither the amount of blood present in brain parenchyma (such as lesion size) nor in the cisternal and ventricular spaces seemed to affect the occurrence of seizures.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…2,7 The incidence of SE after stroke either is low or is not cited at all in some reports. [1][2][3][4][5][17][18][19][20] Three studies reported the rate of SE as 19%, 17%, and 14%. 7,21,22 We found that SE occurred in 9% of all patients admitted for a PFS to our Neurology Department.…”
Section: Discussionmentioning
confidence: 99%
“…2 A brief course of anticonvulsant therapy after lobar ICH may reduce the risk of early seizures. 3 The published incidence of seizures after ICH varies widely from Ͻ10%, 4,5 to 10% to 20%, 6 to Ͼ20%. 7 Many seizures are detected only with electroencephalographic monitoring.…”
mentioning
confidence: 99%